2014
DOI: 10.1002/ana.24030
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐synaptic axonal degeneration in the visual pathway in multiple sclerosis

Abstract: Our results suggest the presence of trans-synaptic degeneration as a contributor to chronic axon damage in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
208
5
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(225 citation statements)
references
References 38 publications
7
208
5
5
Order By: Relevance
“…(2016) and due to the cross‐sectional design, our study does not allow to provide an explanation of the pathophysiology leading to the observed correlation patterns. From a pathophysiologic point of view, the association between OCT outcomes and focal cortical volume might be explained by anterograde and retrograde neurodegeneration within the visual system and its connections to major integrating network hubs (Gabilondo et al., 2014). Steenwijk and colleagues called this a “second‐order effect” where focal neurodegeneration leads to accentuate gray matter loss in important network hubs along defined anatomical structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2016) and due to the cross‐sectional design, our study does not allow to provide an explanation of the pathophysiology leading to the observed correlation patterns. From a pathophysiologic point of view, the association between OCT outcomes and focal cortical volume might be explained by anterograde and retrograde neurodegeneration within the visual system and its connections to major integrating network hubs (Gabilondo et al., 2014). Steenwijk and colleagues called this a “second‐order effect” where focal neurodegeneration leads to accentuate gray matter loss in important network hubs along defined anatomical structures.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with the macular RNFL (mRNFL) thickness, combined ganglion cell layer and inner plexiform layers (GCIPL) thickness appear to have a better but still only moderate correlation with gray matter volume which is linked to disability in MS (Balcer et al., 2015). Moreover, OCT and MRI are promising tools to detect anterograde neurodegeneration after acute optic neuritis as well as retrograde neurodegeneration due to MS lesions in the posterior visual pathway (Gabilondo et al., 2014; Klistorner et al., 2014). How other functional networks aside from the primary visual system might be associated with neuronal loss within the anterior visual system has not been analyzed in depth (Saidha et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…9,31,32 In reality, axonotemesis in the hard-wired visual pathways will always lead to bidirectional transsynaptic axonal degeneration. 33 One should allow a 3-month interval after an acute attack of optic neuritis before attempting to quantify peripapillary atrophy of the RNFL.…”
Section: Thinningmentioning
confidence: 99%
“…7,8 In this Review, we emphasize that optic neuritis represents a pragmatic model for testing structural-functional relationships. 9,10 The visual system is the best-understood and most accessible part of the human CNS. In each eye, 100 million rod photoreceptors capture light, which is then converted by 12 types of bipolar cell into a digitally coded electrical signal, 11 which passes through the 1,158,000 axons of the optic nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond focal axonal damage and its direct mid-term consequences, the question has emerged as to whether trans-synaptic degeneration may play an additional significant role in chronic disease development and neurodegeneration [23]. Subclinically silent tissue destruction following inflammatory damage due to ON or white matter lesions may serve as an example for white matter destruction in MS in general.…”
Section: Ms Visual Pathway White Matter Damage Patternsmentioning
confidence: 99%